Could SCUBE-1 be a marker for subclinical atherosclerosis other than carotid artery intima-media thickness in patients with psoriasis? - Havva Hilal Ayvaz Çelik; Mevlüt Serdar Kuyumcu; Fevziye Burcu Şirin; Mehmet Cirit; Selma Korkmaz; İjlal Erturan; Seda Çelik; Mehmet Yıldırım (Sociedade Brasileira de Dermatologia, 2023)
Abstract Background Psoriasis is a chronic inflammatory disease that is associated with many inflammatory conditions such as atherosclerosis, hypertension, among others. SCUBE-1 is a protein that plays a role in angiogenesis. Objectives The present study aimed to investigate whether SCUBE-1 could indicate subclinical atherosclerosis in psoriatic patients, and to compare SCUBE-1 levels, measurement of carotid artery ıntima-media thickness (CIMT), and metabolic parameters in psoriasis patients and healthy controls. Methods Forty-six patients with psoriasis and 43 healthy controls were included. The severity of the disease was assessed with Psoriasis Area Severity Index (PASI) in the patient group. Levels of SCUBE-1, CRP, lipids, and fasting glucose were measured with the enzyme-linked ımmunosorbent assay (ELISA) method, and CIMT measurements were performed by the same cardiologist. Results SCUBE-1 levels and CIMT values were significantly higher in the patient group (for both p < 0.05). Moreover, systolic blood pressure, CRP levels, and waist circumference were higher in the patient group even though both groups had similar BMIs (for all p < 0.05). A positive correlation was found between SCUBE-1 and CIMT values among patients, and multiple regression analyses revealed that SCUBE-1 and CIMT are significantly associated with psoriasis as well. Study limitations A low number of participants and not including any other inflammatory marker related to angiogenesis or atherosclerosis such as VEGF, adiponectin are the main limitations of the present study. Conclusion Despite the severity of the disease, even in psoriasis patients with mild disease the SCUBE-1 level may be an indicator of subclinical atherosclerosis and indicate the risk of cardiovascular disease in the future.